A Novel Carbon Fiber Composite Material for the Simulation of Damage Evolution in Thick Aquifers - Bozhi Zhao; Xing Gao; Weibing Zhu; Jiaxing Ding; Pengjun Gao (Applied Sciences)
Simulation experiments are a crucial method for investigating overburden failure, strata movement, and strata control during coal mining. However, traditional similar materials struggle to effectively monitor internal damage, fracturing, and dynamic development processes within the strata during mining. To address this issue, carbon fibers were introduced into the field of similar material simulation experiments for mining. Leveraging the excellent conductivity and the sensitive feedback of resistivity changes in response to damage of this composite material enabled real-time monitoring of internal damage and fracture patterns within the mining strata during similar simulation experiments, leading to the development of a carbon fiber similar simulation composite material with damage self-sensing properties. This study found that as the carbon fiber content increased, the evolution patterns of the electrical resistance change rate and the damage coefficient of the similar material tended to coincide. When the carbon fiber content in the similar material exceeded 2%, the electrical resistance change rate and the damage coefficient consistently exhibited synchronized growth with identical increments. A similar simulation experiment revealed that after the completion of workface mining, the thick sandstone aquifer did not develop significant cracks and remained stable. In the early stages of mining, damage rapidly accumulated at the bottom of the thick aquifer, approaching the failure threshold. In the middle layers, a step-like increase in the damage coefficient occurred after mining reached a certain width, while the top region was less affected by mining activities, resulting in less significant damage development. The research findings offer new experimental insights into rock layer movement and control studies, providing theoretical guidance for the prediction, early warning, and prevention of dynamic disasters in mines with thick key layers.